Formasi Tempat Duduk terhadap Hasil Belajar Siswa Kelas VII - Clara Amelia; Arwin Achmad; Rini Rita T. Marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2017)
Thepurpose of this study was to find out effectiveness of seating formation towards students learning outcomes on the interaction between organisms and their environment subject on junior high school 1 Pesawaran.The design of research was pretes-postes non equivalent. The samples of grade VIIA, VIIB, VIIC were selected by purposive sampling technique from the population that were the entire class VII. The research data were quantitative of cognitive aspect that were obtained from pretest and postes which were statistically analyzed by One-way Anova and t-test, qualitative data were affective and psychomotor aspect that were obtained from student's self-assessment and skill observationwhich were analyzed with increasing value and IPK. The result of each aspect showed that the experimental class I has N-gain and the highest increase in value. Therefore, there are differences in the effectiveness of the three seating formations applied towards student learning outcomes.Penelitian ini bertujuan untuk mengetahui efektivitas formasi tempat duduk terhadap hasil belajar siswa pada materi interaksi antar makhluk hidup dan lingkungannya di SMPN 1 Pesawaran. Desain penelitian pretes-postes non ekuivalen. Sampel kelas VIIA, VIIB, VIIC dipilih dengan teknikpurposive sampling dari populasi yaitu seluruh kelas VII. Data penelitian berupa data kuantitatif yaitu aspek kognitif diperoleh dari pretes dan postes yang dianalisis secara statistik denganOne-way Anovadan uji-t, data kualitatif yaitu aspek afektif dan psikomotorik diperoleh dari penilaian diri siswa dan pengamatan keterampilan yang dianalisis dengan peningkatan nilai dan IPK. Hasilnya pada setiap aspek menunjukkan kelas eksperimen I memiliki N-gain dan peningkatan nilai tertinggi. Oleh karena itu, terdapat perbedaan efektivitas dari ketiga formasi tempat duduk yang diterapkan terhadap hasil belajar siswa.Kata kunci: efektivitas, formasi tempat duduk, hasil belajar